Solve the simultaneous equations 4π₯ – y = 7 and 3π₯ + 2y = 19

=

π₯

,

=

y

Correct

5π₯ + 6y = -11
7π₯ + 5y = 5

25π₯ + 30y = -55 Multiply the first equation by 5 and the second equation by 6 to give
42π₯ + 30y = 30 the same number of y's in each equation

17π₯ = 85 Subtract the first equation from the second equation to eliminate y
(30 – -55 = 85)
So π₯ = 85 ÷ 17
= 5

5 × 5 + 6y = -11 Substitute the value of π₯ we have found into the first equation
25 + 6y = -11
6y = -11 – 25 Take 25 away from both sides
6y = -36
y = -36 ÷ 6 Divide both sides by 6
= -6